On the fair management of close races in swimming - Faux, D. A.; Godolphin, J. D. (Journal of Swimming Research, 2020)
The sport of swimming faces particular problems of adjudication for close races. Swimming cannot benefit from technology in the same way as athletics and other sports in which photo finishes and visual differentiation is used to determine ranking. Swimming at the highest level relies almost entirely on the electronic timing system and displayed race times, presented to the nearest 0.01s, to determine the ranking of swimmers and to establish if a dead heat has occurred. At swimming events, electronic timing equipment records individual race times to 0.0001s. However, it is shown that any protocol used to display race times to the nearest 0.01s leads to unfairness in the categorization of a race as a dead heat. The key issues are discussed in the context of the controversial Michael Phelps and Milorad Cavic 100m butterfly event at the 2008 Beijing Games. An alternative approach for the categorization of a dead heat is proposed which is fairer to swimmers.